Perancangan Tambang (Pit Design) dan Pentahapan Tambang Batubara Pit Blok 3 dengan Stripping Ratio 7 : 1 di PT XYZ, Desa Lubuk Sini, Kecamatan Taba Penanjung, Kabupaten Bengkulu Tengah, Provinsi Bengkulu - Ahmad Khairul (Bandung Conference Series: Mining Engineering, 2021)
Abstract. The research was conducted at PT XYZ located in District of Taba Penanjung, Central Bengkulu Regency, Bengkulu Province. The purpose of this study, to make the pit design with economical SR, determines the mined reserves and mine life in the study area. The result of coal resource estimation from modeling result is 36.634.596 ton. The parameters needed to design Pit Block 3 are, among others, geometry of mining slope, pit limit, mine road, and economical stripping ratio (stripping ratio). Based on the calculation of BESR II (Break Even Stripping Ratio) and economical SR calculation at PT XYZ, it is found that the economic potential limits of stripping ratio is 1: 7. Therefore Pit Block 3 is designed in the center of IUP PT XYZ with depth Maximum Pit 79 meters and total open area of Block 3 pit 3 of 113 Ha with SR design <7. Based on the design optimization, the coal reserve in Pit Block 3 PT XYZ is 4,822,411 tons with an overburden volume of 34,097,854 BCM. The production target of PT XYZ per month is 57,990 ton / month and with SR 1: 7 it is necessary to peel overburden 405,927 bcm / month. So get the age of pit block 3 is for 6 years 11 months ≈ 7 years. Where for annual mine sterling total reserves of mined amounted to 695,875 tons of coal and 4,871,122 bcm overburden. Abstrak. Penelitian dilakukan di PT XYZ yang berada di Kecamatan Taba Penanjung, Kabupaten Bengkulu Tengah, Provinsi Bengkulu. Tujuan dari penelitian ini, untuk membuat rancangan pit dengan SR ekonomis, menentukan cadangan tertambang dan umur tambang di daerah penelitian. Hasil estimasi sumberdaya batubara dari hasil pemodelan sebesar 36.634.596 ton. Adapun parameter yang diperlukan untuk merancang Pit Blok 3 tersebut, diantaranya geometri lereng tambang, batas penambangan (pit limit), jalan tambang, dan nisbah kupas (stripping ratio) yang ekonomis. Berdasarkan hasil perhitungan BESR II (Break Even Stripping Ratio) dan perhitungan SR Ekonomis di PT XYZ diperoleh batas potensial ekonomis nisbah kupas yaitu 1 : 7. Oleh karena itu Pit Blok 3 yang dirancang berlokasi di bagian tengah IUP PT XYZ dengan kedalaman maksimal Pit 79 meter dan luas bukaan keseluruhan pit Blok 3 sebesar 113 Ha dengan SR desain <7. Berdasarkan optimasi desain, maka didapat cadangan batubara pada Pit Blok 3 PT XYZ adalah 4.822.411 ton dengan volume overburden 34.097.854 BCM. Target produksi PT XYZ per bulannya adalah sebesar 57.990 ton/bulan dan dengan SR 1:7 maka perlu mengupas overburden sebanyak 405.927 bcm/ bulan. Sehingga didapat umur pit blok 3 ini selama 6 tahun 11 bulan ≈ 7 tahun. Dimana untuk pentahapan tambang pertahun total cadangan tertambang adalah sebesar 695.875 ton batubara dan 4.871.122 bcm overburden.